DIRECT-PROSPECTING TECHNOLOGY OF SATELLITE AND PHOTO IMAGES FREQUENCY-RESONANCE PROCESSING: RESULTS OF APPROBATION ON PROSPECTING BLOCKS AND SITES OF WELLS FOR HYDROGEN DRILLING IN FRANCE - Mykola Yakymchuk; Ignat Korchagin; Valery Solovyov (World Scientific Reports, 2026)
To demonstrate the operability and efficiency of direct-prospecting technology of frequency-resonance processing and interpretation of satellite images and photographs, the results of its testing within large blocks of hydrogen degassing and local areas of wells drilling in France are presented and analyzed. The developed and used mobile and low-cost technology include modified methods of frequency-resonance processing and decoding of satellite and photo images, vertical electric-resonance sounding (scanning) of a cross-section, as well as a method of integrated assessment of the prospects of hydrocarbons and hydrogen potential of large prospecting blocks and license areas. Separate methods of this direct-prospecting technology are based on the principles of the “substance” paradigm of geophysical research, the essence of which is to search for a specific substance - oil, gas, hydrogen, gold, zinc, etc. The surveyed in reconnaissance mode big blocks and local areas in different region of France are promising for detailed prospecting and drilling wells for natural hydrogen. Conclusions and recommendations of this nature were made taking into account the results of large-scale testing of direct-prospecting methods in areas and sites of visible hydrogen degassing in various regions of the globe. In the process of analyzing and comparing the results of the reconnaissance survey of the “Trois Evêchés” license block, local areas within it and implementing additional instrumental measurement procedures, a site with a basaltic volcanic structure was localized, within which 12 hydrogen-saturated layers were recorded by sounding the cross-section interval of 0-5 km. To further demonstrate the feasibility of the methods used, the article includes also the results of a reconnaissance survey of a hydrogen production site in Mali and detailed studies to locate sites for well drilling in Ukraine. Instrumental measurements have revealed the presence of a basaltic volcanic complex at a hydrogen production site in Mali. Fine-grained scanning of the section within a wellbore image at intervals of 0-2 km revealed 11 hydrogen-bearing strata of varying thickness. Within the survey block in Ukraine, during the frequency-resonance processing of satellite images of local sites of different areas in detailed mode (format), a zone of accumulation of hydrogen and living (healing) water was detected and localized. In the process of crushing satellite images into fragments of different sizes, the most promising zones (sites) for drilling exploratory wells were detected and localized. By scanning the section with steps of different sizes the thickness and depth of the most promising reservoirs with hydrogen, as well as living (healing) water were determined. The materials of the article, as well as the previously published results of experimental studies in various regions, indicate the advisability of using low-cost methods of frequency-resonance processing of satellite images and photographs to detect zones of hydrogen accumulation in areas of basalt volcano’s location, as well as in areas of hydrogen degassing. Detailed studies and drilling of wells in promising areas can be planned and carried out for hydrogen and living water at the same time. The obtained results of experimental work are also additional evidence in favor of "volcanic" model of the formation of various structural elements and the external appearance of the Earth, as well as deposits of combustible and ore minerals (including hydrogen and water). The use of mobile and low-cost technology will significantly speed up the exploration process for hydrogen, as well as reduce the financial costs for its implementation